PLURALISME HUKUM DAN SISTEM PERKAWINAN WONG SIKEP - Tine Suartina (LIPI Press, 2014)
Marriage,as a holy tie between persons, can be analysed from two perspectives: as a tradition and an aspect regulated by state law. In a certain circumstance, the tradition of marriage can be different or even in opposition to state’s marriage formal law. The marriage system of Wong Sikep in several regions in Central and East Java Provinces can be seen as one important example. Based on library research, this article analyzes the issue of legal pluralism that potentially occurs because of the implementation of multi laws in a certain field in a society - state law and adat law -. It shows how Wong Sikep communities respond differently to marriage formal system implementation, part of them still practice their adat law purely and some others who have conducted adjustment with state’s (marriage) law. Keywords: marriage, Wong Sikep, Samin, legal pluralism